Superalloys 2008 (Eleventh International Symposium) 2008
DOI: 10.7449/2008/superalloys_2008_405_414
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of γ' Particle Size on the Deformation Mechanism in an Advanced Polycrystalline Nickel-Base Superalloy

Abstract: The deformation mechanisms under tensile loading in a 48 vol.% γ′ polycrystalline nickel-base superalloy (RR1000) have been studied in-situ using neutron diffraction at 20°C, 500°C and 750°C. In addition, post-mortem microstructural studies were carried out on deformed samples using an ultra high resolution field emission gun scanning electron microscope (FEGSEM). Deformation studies were carried out on three different model microstructures with a uni-modal γ′ mean particle size of 80 nm, 120 nm and 250 nm. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 19 publications
(11 reference statements)
2
21
0
1
Order By: Relevance
“…Previous work on RR1000 has shown that as the precipitate size decreases, onset of load partitioning occurs at increased levels of plastic strain [8]. The diffraction data for Alloy 720Li shows a similar trend.…”
Section: Misfit Strain and Load Partitioningsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous work on RR1000 has shown that as the precipitate size decreases, onset of load partitioning occurs at increased levels of plastic strain [8]. The diffraction data for Alloy 720Li shows a similar trend.…”
Section: Misfit Strain and Load Partitioningsupporting
confidence: 64%
“…To date, most work has attempted to relate γ' size distributions to mechanical properties [9] but without considering misfit. It has also been shown that deformation temperature [10] and precipitate size [8] have very significant impact on the level of load partitioning between γ and γ' during deformation in both Alloy 720Li or RR1000. In this paper, the focus is on the effect of the γ/γ' lattice misfit.…”
Section: Introductionmentioning
confidence: 99%
“…Neutron and synchrotron X-ray diffraction experiments coupled with in-situ loading are extremely helpful in understanding phase-level and grain-level lattice strain and stress in Ni-base superalloys [11][12][13][14][15]. Preuss et al coupled neutron diffraction with tensile loading to study the role of γ' particles during high temperature deformation.…”
Section: Neutron Diffraction Studies In Superalloysmentioning
confidence: 99%
“…The chemical composition of this alloy is related to that of GH720 (UDIMET 720) from which it is derived, but differs from it with respect to the chromium, carbon and boron levels. Till now, a lot of studies [1][2][3][4][5][6] have been done for GH720Li alloy including the solutioning and precipitating of γ prime phase, the ingot to billet conversion process control, the heat treatment schedule optimizing, the mechanical behavior under service conditions, etc. However, the microstructure of GH720Li consists of primary, secondary and tertiary γ′ due to its special heat treatment schedule.…”
Section: Introductionmentioning
confidence: 99%